Protection of Third Party Preferential Rights in the Confiscation of Corruption Crime Assets in Indonesia - Rini Purwandari; Shinta Hadiyantina; Bambang Sugiri (State Islamic University of North Sumatra Indonesia, 2025)
Corruption in Indonesia is not only understood as a criminal act that harms state finances, but also as a violation of human rights, especially when assets resulting from corruption are confiscated but are found to be controlled by third parties acting in good faith. This study aims to analyze the meaning of legal regulations related to the protection of third-party preferential rights and to formulate an ideal regulatory concept for the future. Using a prescriptive-analytical normative juridical method, this study examines legislative approaches, case studies, and court decisions. The results show that the existing legal framework, including the PTPK Law and Supreme Court Regulation No. 2 of 2022, does not provide comprehensive guarantees for the rights of third parties. The case studies of Bank Jatim and PT Sritex reveal a legal vacuum in practice, where legitimate secured creditors remain vulnerable when assets are confiscated. This study concludes that without clear and synchronized regulations, asset seizure has the potential to create new injustices, undermine public trust, and disrupt legal certainty in economic activities. Therefore, the reconstruction of more adaptive and transparent regulations is an urgent need to balance the interests of the state in asset recovery and the protection of bona fide third parties.